MINI REVIEW : SINTESIS KOMPOSIT Fe3O4/ARANG AKTIF SEBAGAI MEDIA ADSORPSI - Laurentha, Nantha; Hindryawati, Noor (PROSIDING SEMINAR NASIONAL KIMIA, 2025)
Mini review of Fe 3 O 4 /activated carbon composite synthesis as adsorption media. The purpose of this mini review is to optimize adsorption efficiency through variations of different types of activated carbon. The Fe 3 O 4 /activated carbon composite is used as adsorption media due to its high adsorption capacity, and the magnetic properties of Fe 3 O 4 facilitate the separation of the composite from the solution after the adsorption process. Based on a literature review, the Fe 3 O 4 /activated carbon composite can be synthesized using the co-precipitation method, and characterization is performed using Fourier Transform Infrared Spectroscopy (FTIR), and X-Ray Diffraction (XRD). Therefore, this article reviews recent developments regarding the Fe 3 O 4 /activated carbon composite as an adsorption medium for dye wastewater.   Keywords : Fe 3 O 4 , activated carbon, composite, adsorption.